Investigating Hgh-School EFL Learners’ Foreign Language Anxiety: A Case Study at SMA 4 Banda Aceh - Zulfikar, Zulfikar (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study aimed to investigate the level of foreign language anxiety (FLA) experienced by senior-high-school English language learners (ELLs) and to explore plausible factors that contribute to the learners’ anxiety. This research employed a qualitative descriptive method with a case study approach, involving thirty-four twelfth-grade ELLs from SMA 4 Banda Aceh, Indonesia, as participants. In gathering the data, Horwitz et al.'s (1986) Foreign Language Speaking Anxiety Scale (FLCAS) and semi-structured interview were used as instruments. The findings revealed that the majority of the ELLs were at a moderate level of anxiety, with more than half of them being at “Mildly Anxious” level and with no “Very Anxious” learners. The findings also indicated that the ELLs’ FLA was caused not only by teacher factors but also student factors. The teacher factors include oral presentation task, incomprehensible input, and teachers’ attitude, while student factors comprise learners’ fear of being laughed at, their’ beliefs about L2, and lack of preparation.